FACTORS AFFECTING EMPLOYEE JOB SATISFACTION - Conie Nopinda Br Sitepu; Ingan Ukur Br Sitepu; Vina Maria Ompusunggu; Jupianus Sitepu (SENSEI RESEARCH CENTER, 2021)
The data used in this research is the primary data obtained directly from the results of a questionnaire distribution by the respondent. The population of this research is the employees of the PDAM Tirtanadi of North Sumatera province Berastagi branch. The sampling technique used is a saturated sampling technique, which is to take the whole of the total population of 38 people. The data analysis used is double linear regression analysis. The results showed that partially the work itself, the supervisor, the co-workers and the promotion as free variables had no significant effect on job satisfaction, while the salary/wage was partially influential positively and significantly towards job satisfaction. Simultaneously the work itself, supervisors, coworkers, promotions and salary/wages have a positive effect and a significant impact on the satisfaction of employees employment Tirtanadi of North Sumatera province Berastagi branch.The data used in this research is the primary data obtained directly from the results of a questionnaire distribution by the respondent. The population of this research is the employees of the PDAM Tirtanadi of North Sumatera province Berastagi branch. The sampling technique used is a saturated sampling technique, which is to take the whole of the total population of 38 people. The data analysis used is double linear regression analysis. The results showed that partially the work itself, the supervisor, the co-workers and the promotion as free variables had no significant effect on job satisfaction, while the salary/wage was partially influential positively and significantly towards job satisfaction. Simultaneously the work itself, supervisors, coworkers, promotions and salary/wages have a positive effect and a significant impact on the satisfaction of employees employment Tirtanadi of North Sumatera province Berastagi branch.